IMPLEMENTASI PERATURAN DAERAH NOMOR 4 TAHUN 2010 TENTANG BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN DI KOTA PEKANBARU - Putri, Hayyu Dwi; Ridwan, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research concluded in communication, indicators that the policy has been issued to do the re-election BPHTB in Pekanbaru was according to the author has yet to show a good policy, In bureaucratic structures indicators are pretty good with formed by power that deal with problems BPHTB so it needs internal coordination in all fields. On the sub resources indicators, the ability to officials in system implementation Perda No. 4 in 2010 was still not and it is very necessary to promote motivation and working spirit from the officials of Regional income Pekanbaru . In this appointment or indicators tendencies members who are found in tax collection fees for acquisition of rights to land and building (BPHTB of Regional income) in Pekanbaru have not yet been held in accordance with the procedure. This can be seen from procedure or The initial Regional Taxes (SSPD BPHTB), and payment procedure BPHTB that in stages the procedure is not in accordance with the rule that is determined. While for the procedure Billing BPHTB did not walk because during in 2011 there was no error in calculating tax, a mistake in writing, or tax that touches interest/fines and tax that has not been fully pay taxes terutangnya. Reduction procedure BPHTB has not yet occurred because of lack of knowledge officers tax collectors and the lack of facilities and infrastructure that supports the process.Key words : Fees For Acquisition Of Rights To Land And Building, Pekanbaru